Fabrication of high-temperature superconducting HgBa2CuO4+delta within silver-sheathed tapes - Peacock, G; Gameson, I; Edwards, P; Khaliq, M; Yang, G; Shields, T; Abell, J (1997)
We report, here, the successful synthesis of the high-temperature superconductor HgBa2CuO4+δ within a silver-sheathed tape, showing a superconducting transition temperature of up to 96 K. We have also identified several control parameters -most notably thermal treatment and cycling - which lead to enhanced superconducting volume fractions within the tapes. The most dramatic effect is that of air-quenching of the sealed tapes from the ceramic synthesis temperature, leading to enhancement of the superconductor phase-purity. In addition, the more subtle, but equally important, factor of thermal cycling at progressively increasing temperatures leads to an increase in the inter-granular connectivity and a stronger magnetic signal. The fabrication of the HgBa2CuO4+δ phase in a silver tape, in this manner, is an important step towards the goal of high-temperature superconducting tapes of the mercury-cuprate materials.